2019
DOI: 10.1002/jbmr.3641
|View full text |Cite
|
Sign up to set email alerts
|

Change in Bone Density and Reduction in Fracture Risk: A Meta-Regression of Published Trials

Abstract: Meta‐analyses conducted >15 years ago reported that improvements in bone mineral density (BMD) were associated with reduction in vertebral and nonvertebral fractures in osteoporosis trials. Numerous studies have been conducted since then, incorporating new therapies with different mechanisms of action and enrolling many more subjects. To extend these prior analyses, we conducted a meta‐regression of 38 placebo‐controlled trials of 19 therapeutic agents to determine the association between improvements in BMD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
154
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(180 citation statements)
references
References 63 publications
3
154
1
5
Order By: Relevance
“…In addition to the likely long-term benefit, a prior study in human cadaveric femurs demonstrated that AGN1 implantation also leads to an immediate increase in femoral strength [18]. Although the sample size does not allow for a statistical assessment of fracture reduction, increased aBMD and femoral strength via FEA correlates with bone strength and fracture risk reduction [19,20,22,23], suggesting that AGN1 LOEP has the potential to reduce hip fracture risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the likely long-term benefit, a prior study in human cadaveric femurs demonstrated that AGN1 implantation also leads to an immediate increase in femoral strength [18]. Although the sample size does not allow for a statistical assessment of fracture reduction, increased aBMD and femoral strength via FEA correlates with bone strength and fracture risk reduction [19,20,22,23], suggesting that AGN1 LOEP has the potential to reduce hip fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence for a strong correlation between aBMD of the proximal femur and hip fracture risk [8,22]. For example, in the HORIZON Recurrent Fracture Trial, which tested whether zoledronic acid would prevent contralateral hip fractures in those who had already suffered one hip fracture, modest increases in femoral neck aBMD (3.6% over 3 years) led to a clinically meaningful and significant 30% decrease in the incidence of hip fractures [24].…”
Section: Discussionmentioning
confidence: 99%
“…Age and BMD were closely related to the occurrence of neck shortening. With increasing age, BMD may decline, and it is clear that bone quality may determine the probability of femoral neck fracture [32]. Reduction of the axial anti-compression strength of the femoral neck leads to its shortening.…”
Section: Discussionmentioning
confidence: 99%
“…Group‐level clinical trial data suggest that larger BMD increases are associated with greater fracture risk reduction . A meta‐regression of published trials found that greater improvements in total hip, femoral neck, and lumbar spine BMD were strongly associated with greater reductions in vertebral fractures . In the clinical trials setting, there may be relatively little value in BMD monitoring because all patients are closely monitored for adherence and there is uniformity in the treatment regimen .…”
Section: Discussionmentioning
confidence: 99%